2017
DOI: 10.1080/0309877x.2017.1301408
|View full text |Cite
|
Sign up to set email alerts
|

Traditional or non-traditional students?: incorporating UK students’ living arrangements into decisions about going to university

Abstract: Since the introduction of the post-1992 university, various, and ongoing, higher education policy reforms have fuelled academic, political, media and anecdotal discussions of the trajectories of UK university students. An outcome of this has been the dualistic classification of students as being from either 'traditional' or 'nontraditional' backgrounds. An extensive corpus of literature has sought to critically discuss how students experience their transition into university, questioning specifically the notio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 55 publications
0
27
1
Order By: Relevance
“…However, some participants had more fluid experiences of moving away in which they wanted to maintain ties to their family home rather than leave their old life behind. Similarly, moving away did not appear to signify a simple break from students' previous identities; whilst Holton (2018) found that students who did not move away from home during university would be more likely to want to retain a sense of their pre-student identities, our findings suggest that even when students do move away, some of them do not necessarily express a desire to change either.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…However, some participants had more fluid experiences of moving away in which they wanted to maintain ties to their family home rather than leave their old life behind. Similarly, moving away did not appear to signify a simple break from students' previous identities; whilst Holton (2018) found that students who did not move away from home during university would be more likely to want to retain a sense of their pre-student identities, our findings suggest that even when students do move away, some of them do not necessarily express a desire to change either.…”
Section: Discussioncontrasting
confidence: 66%
“…The first theme from our thematic analysis highlights that many of the participants moved away from home for the "student experience" (Holton 2018), anticipating that they would become more independent as part of the need to grow up. This perspective reinforces traditional depictions of the 'planned' 'student pathway' of moving out of the family home (Rugg, Ford, and Burrows 2004) and shows the impact of such cultural expectations upon students' conceptions of becoming a student.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research has shown that commuting students vary their levels of engagement based on whether or not they are living with their parents [48,49]. Low network warp, i.e., low street connectivity, is strongly associated with suburban areas of the city [24].…”
Section: Discussionmentioning
confidence: 99%
“…Prestigious universities tend to socially and culturally reproduce certain sectors of society with relatively high levels of cultural and economic capital (Bourdieu & Passeron, 1979). In the UK such geographies tend to be tied to practices of mobility and migration, where young people move away from home and stay in student accommodation to study (Holdsworth, 2009;Kinton et al, 2018;Smith & Hubbard, 2014), although more diverse residential student geographies are emerging (Holton, 2018;Wakeling & Jefferies, 2012). Differentiated student cultures exist even within traditional and seemingly homogenous student intakes (Holton and Riley, 2016; see also Finn & Holton, 2019).…”
Section: Contextualising Young Women Undergraduate's Expectations Of Gendered Work Spacesmentioning
confidence: 99%